SPEAKING ENGLISH PERFORMANCE ASSESSMENT WITH THE FACET RASCH MEASUREMENT MODEL - Hidayat, Wahyu; Anzali, M. Noor; Turmudi, Muhammad (Jurnal Evaluasi Pendidikan, 2023)
This study aims to assess students' English-speaking abilities based on peer assessment. This study is a quantitative study involving 10 students. Data was collected using tests and student speaking assessment rubrics with score criteria from 1 to 5. Speaking assessment criteria are pronunciation, grammar, vocabulary, fluency and understanding. Data were analyzed using Many Faceted Rasch Measurement (MFRM). The Facets Rasch Measurement model is able to see the interaction between respondents and items at once. The research results show that the item index for criteria/quality (6.39), speaker (0.51), and rater (5.32) as well as the standard deviation value clearly shows a good distribution of item difficulty. Criterion reliability is 0.98 for raters is 0.21, for raters is 0.97.